Insult and Politics in Divergent Discourse:Case Study of the FARC-EP - Cediel Gómez, Yulia Katherine; Olave Arias, Giohanny (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This is a research about a corpus composed by communications of the guerrilla Fuerzas Armadas Revolucionarias de Colombia- Ejército del Pueblo (FARC-EP), which was published between 2010 and 2012. The objective is to analyze the political dimen- sion of the vituperation in the insurgent discourse. Through an inductive method, from grounded theory, the research describes the uses of utterances as an insult against the opponents, which are created by the insurgent discourse. Foremost, the research identi- fies the social and historical emergence conditions of the vituperative rhetoric. Then the research determinates the destination of the insults and, finally, shows how those uses are related with the polemic dimension of the public communications. The conclusion of the research is that the insult uses allowed the FARC-EP to create a parresiastic ethos, as a preparation for the insertion in the democratic system, where is becoming more common the use of the insults to get voters